Ìpàdé with Maestra Iara Deodoro: memories from the Afro-Sul Group, a piece of Africa in the South of Brazil - Alves Neto, Manoel Gildo; Silva, Suzane Weber da (Revista Brasileira de Estudos da Presença, 2021)
This paper follows the journey of the Black artist Maria Iara Santos Deodoro and her artistic-pedagogical work with the Afro-Sul Music and Dance Group. It also reflects and contextualizes certain events and topics in the debate on ethnic-racial relations concerning the Performing Arts in southern Brazil and further exchanges. Corporeality, orality, and musicality intertwined with dance are discussed as Afro-oriented perspectives practiced by the Afro-Sul Group in the fight against racism.